Prevalence of sarcopenia in patients with chronic kidney disease: a global systematic review and meta‐analysis - Marvery P. Duarte; Lucas S. Almeida; Silvia G.R. Neri; Juliana S. Oliveira; Thomas J. Wilkinson; Heitor S. Ribeiro; Ricardo M. Lima (Wiley, 2024)
Abstract Sarcopenia is a risk factor for adverse clinical outcomes in chronic kidney disease (CKD) patients, including mortality. Diagnosis depends on adopted consensus definition and cutoff values; thus, prevalence rates are generally heterogeneous. We conducted a systematic review and meta‐analysis to investigate the global prevalence of sarcopenia and its traits across the wide spectrum of CKD. A systematic search was conducted using databases, including MEDLINE and EMBASE, for observational studies reporting the prevalence of sarcopenia. We considered sarcopenia according to the consensus definition of the European Working Group on Sarcopenia in Older People (EWGSOP), the Asian Working Group for Sarcopenia, the Foundation for the National Institutes of Health Sarcopenia Project, and the International Working Group on Sarcopenia (IWGS). Subgroup analyses by CKD stages, consensus, and gender were performed. Pooled prevalence was obtained from random‐effect models. A total of 140 studies (42 041 patients) across 25 countries were included in this systematic review and meta‐analyses. Global prevalence of sarcopenia was 24.5% [95% confidence interval (CI): 20.9-28.3) and did not differ among stages (P = 0.33). Prevalence varied according to the consensus definition from 11% to 30%, with no significant difference (P = 0.42). Prevalence of severe sarcopenia was 21.0% (95% CI: 11.7-32.0), with higher rates for patients on dialysis (26.2%, 95% CI: 16.6-37.1) compared to non‐dialysis (3.0%, 95% CI: 0-11.1; P < 0.01). Sarcopenic obesity was observed in 10.8% (95% CI: 3.5-21.2). Regarding sarcopenia traits, low muscle strength was found in 43.4% (95%CI: 35.0-51.9), low muscle mass in 29.1% (95% CI: 23.9-34.5), and low physical performance in 38.6 (95% CI: 30.9-46.6) for overall CKD. Prevalence was only higher in patients on dialysis (50.0%, 95% CI: 41.7-57.4) compared to non‐dialysis (19.6%, 95% CI: 12.8-27.3; P < 0.01) for low muscle strength. We found a high global prevalence of sarcopenia in the wide spectrum of CKD. Low muscle strength, the primary sarcopenia trait, was found in almost half of the overall population with CKD. Patients on dialysis were more prevalent to low muscle strength and severe sarcopenia. Nephrology professionals should be aware of regularly assessing sarcopenia and its traits in patients with CKD, especially those on dialysis.